Visum Et Repertum As Evidence In Uncovering The Occurrence of Criminal Acts - Putri, Nawang; Sularto, RB (Devotion : Journal of Research and Community Service, 2023)
The criminal law evidentiary system in Indonesia is a negative wettelijk or proof sys-tem based on the Law negatively. To make light of a criminal act, valid evidence is needed according to the Criminal Procedure Code as stated in Article 184 paragraph 1 of the Criminal Procedure Code. Not all criminal acts can be proven with the naked eye. For example, evidence related to bodily injuries or that cause health problems, or that result in the death of a person. Without expert help a law enforcement officer cannot conclude this. the purpose of this research is to find out visum et repertum as evidence in uncovering the occurrence of criminal acts. This research is a legal research that uses a normative or doctrinal juridical ap-proach by collecting and analyzing secondary data. So it is necessary to help the medical science of the judiciary to deal with the problem. Forensic doctors assist in processes related to judicial proceedings. And the results of the examination are poured into Visum et Repertum. In criminal cases Visum et Repertum is used instead of corpus delicti. That visum et repertum is valid evidence in accordance with article 184 of the Penal Code as evidence of letters